Peran Kebijakan Dividen dalam Memoderasi Pengaruh Struktur Modal, Profitabilitas, dan Likuiditas terhadap Nilai Perusahaan - Imilda; Hajriyanti, Rahmi; Zahra, Rita (Jurnal Manajemen dan Teknologi, 2025)
This study examines the role of dividend policy in moderating the effect of capital structure, profitability, and liquidity on firm value. A quantitative approach was used, with Tobin's Q to measure firm value, Debt Equity Ratio (DER) for capital structure, Return on Assets (ROA) for profitability, and Current Ratio (CR) for liquidity. Dividend policy was measured using the Dividend Payout Ratio (DPR) as a moderating variable in the relationship between capital structure, profitability, and liquidity with firm value. Data was obtained from the annual financial statements of companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. Multiple linear regression analysis was applied to test the relationships among these variables. The results show that dividend policy plays a role in moderating the relationship between capital structure and firm value. However, the effect of dividend policy on the relationship between profitability and firm value was not significant. Liquidity also did not show a significant effect on firm value in this model. This study emphasizes the importance of dividend policy in the efficient management of capital structure to enhance firm value. These findings provide guidance for strategic decisions in determining dividend policies to improve financial performance.